The Influence of Cultural Acculturation on the Communication Behavior of the Bugis Community in Boroko Utara Village, Bolaang Mongondow Utara Regency - Tolapa, Minarni (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
This study aims to determine the influence of cultural acculturation on the communication behavior of the Bugis community in Boroko Utara Village. The research design employed in this study is quantitative, utilizing a survey method. There were 42 samples in this research. The data analysis method used simple regression analysis. The study's results indicate that cultural acculturation significantly influences the communication behavior of the Bugis community in Boroko Utara Village, with a coefficient of 0.626 or 62.6%. This is attributed to the Bugis community's long-term adaptation. For instance, the Bugis community has embraced the customs and traditions of the Boroko Utara Village community. Additionally, factors such as rapid speech delivery, adaptability, self-confidence, and historical relationships have contributed to the Bugis community's integration into the Boroko Utara Village community. The greater similarity between Bugis and Boroko Utara Village cultures, which constitute their new environment, facilitates and accelerates cultural acculturation, consequently affecting changes in their communication behavior.